Portugues como língua estrangeira e tecnologias digitais: uma experiência com o grupo de discussao On-Line no contexto do PEC-G - Simone Garofalo Carneiro (2014)
With its political and economic growth, Brazil has received a large number of foreigners of different nationalities. These foreigners come to Brazil for different reasons, such as the completion of studies at the university level. In this context, several agreements were signed between Brazil and other countries for the exchange of students, including the Program for Undergraduate Students-Agreement (PEC-G), which allows foreign citizens to undertake their studies in Brazil. One of the requirements for the foreigner student to carry out its course in Brazilian universities is to obtain the Certificate of Proficiency in Portuguese for Foreigners - Brazil (CELPE-BRAS). However, some participating countries do not apply the proficiency examination. Therefore, the Ministry of Education established a course in Portuguese as a foreign language, held in Brazil and for students from those countries. This is a one-year course, which provides students with knowledge of portuguese language and brazilian culture, so they can obtain the certificate. The Universidade Federal de Minas Gerais (UFMG), one of the institutions of the PEC-G, annually offers this course, which is part of the experience analyzed in this study. This experience is the inclusion, alongside the classroom, of the tool on-line discussion group on two classes of the course, in the years 2009 and 2010. The analysis focuses on a sample of messages exchanged between students and teachers in both on-line discussion groups, aiming to verifying the use of this tool for the acquisition of new language. From the standpoint of theoretical and methodological treatment of data, the analysis is based mainly on the criteria for assessing the proficiency exam and on authors dealing with the use of technological resources in the classroom, the teaching of languages through the digital technology, and the teaching of Portuguese as a Foreign Language.